Conflitos e possibilidades entre atividade minerária e geoconservação na área do Geoparque Costões e Lagunas - RJ - Dias, Laura Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Mining and Geoconservation have different goals for the geodiversity elements. The mining activities take the abiotic resources as an asset to be explored that can be measured economically. On the other hand, the geoconservation objective the protection of geological heritage, a basic and essential requirement for the geoparks seal at UNESCO. Considering that in Brazil there are no specific legal instruments for the protection of geodiversity, there is a legal uncertainty as to geoconservation in the geoparks. This work brings to discussion the impasses that can exist between mining activities and geoconservation, especially in the area of the Costões e Lagunas Geopark in the Rio de Janeiro, showing the possible conflicts and listing the possibility of harmonizing both activities. To raise the possible conflicts between mining and geoconservation, images from Google Earth were used, on which were superimposed the DNPM mining polygonal and geosites location coordinates in order to locate the areas of intersection between the geological sites and the mining processes. From the individual investigation of the 30 geosites at the geopark, it was found that 13 are located in areas required by mining titles or near them. At these points the risks are only potential, since most processes are in the requirement phase or exploration authorization. The risk can become real if the mining will be authorized. Based on this information it was performed a mapping of points of conflict as support for the implementation of protection strategies prior to the installation of the mining. To establish a connection between mining and the geopark activities, it was proposed the deployment of miners geosites, based on international experiences that integrate the geotourism to visitation of mining sites. Therefore, the products of the mineral activity are essential to the development of society, and the human being cannot be dissociated of them, it is important ...

Mineração e Geoconservação possuem objetivos diferentes para com os elementos da geodiversidade. As atividades minerárias tomam os recursos abióticos como um bem a ser explorado e que pode ser mensurado economicamente. Por outro lado, a geoconservação objetiva a proteção do patrimônio geológico, um requisito básico e essencial para a chancela de geoparques junto à UNESCO. Considerando que no Brasil não temos instrumentos legais específicos para a proteção da geodiversidade, há uma insegurança jurídica quanto à geoconservação nos geoparques. Este trabalho traz à discussão os impasses que podem existir entre as atividades minerárias e a geoconservação, especialmente na área do Geoparque Costões e Lagunas no Rio de Janeiro, evidenciando os possíveis conflitos e elencando a possibilidade de harmonizar ambas as atividades. Para levantar os possíveis conflitos entre a mineração e a geoconservação foram utilizadas imagens do Google Earth, sobre as quais foram sobrepostas as poligonais de mineração do DNPM e as coordenadas de localização dos geossítios, a fim de localizar as áreas de intercessão entre os sítios geológicos e os processos minerários. A partir da averiguação individual dos 30 geossítios do geoparque, verificou-se que 13 estão situados em áreas requeridas por títulos minerários ou próximos a elas. Nestes pontos os riscos são apenas potenciais, pois a maioria dos processos se encontra em fase de requerimento ou autorização de pesquisa. O risco pode se tornar real caso as minerações sejam autorizadas. Com base nestas informações foi realizado um mapeamento dos pontos de conflitos como subsídio para a implantação de estratégias de proteção anteriormente à operações minerárias. Para estabelecer uma conexão entre mineração e as atividades do geoparque, foi proposta a implantação de geossítios mineiros com base em experiências internacionais que integram ao geoturismo..
Keywords: Geology; Geoparque Costões e Lagunas (RJ); Geologia; Geoparques - Rio de Janeiro (Estado); Geodiversidade; Minas e recursos minerais; Legislação